Studi perkuatan lentur balok beton bertulang menggunakan GFRP (Glass fiber reinforced polymer) dan WM (wiremesh) - Nalarita, Klara -; Isneini, Mohammad; Alami, Fikri (Universitas Lampung, 2019)
This study discusses flexural strengthening of reinforced concrete beams using GFRP (glass fiber reinforced polymer) and wiremesh. The beams are used have dimensions of length 1.7 m, width and height of 15 cm. Beams were tested with two-point system load using a loadingframe. Two types of retrofitting done in this study is the first type of reinforcement used 4 ply GFRP and retrofitting of the second type by using three layers of GFRP and 1 layer wiremesh. The 6 bars are tested, namely two beams without reinforcement, two beams by using reinforcement beam type 1 and 2 by using the retrofitting of type 2.Based on these results, reinforced beams can be increased up to 146% of the beam without reinforcement. Without reinforcement beam flexural failure with crack spreads at constant torque region and enlarged cracks only at one place in the area. While beams with reinforcement debonding all experienced failure at one end reinforcement. Based on the indexvalue of the beam ductility without retrofitting more ductile than the beam using the retrofitting.Keyword: Concrete, GFRP, Wiremesh, debonding, ductility